Levels and trends of farm families' nonagricultural incomes at different stages of monsoon development - Oshima, Harry T. (The Philippine Review of Business and Economics, 1985)
This paper brings together available data and studies on off-farm activities in Japan, Taiwan, South Korea and other Asian counties and examines the forces underlying the levels and trends of nonagricultural incomes. Nonagricultural activities is defined here as all activities in the industrial and service sectors. The focus of the analysis is that of farm families and their annual incomes. The paper presents estimates of the shares of nonagricultural incomes of farm families for Asian countries for which data are available. It also describes the growth of nonagricultural shares and their composition as the economy moves from one stage to another in various stages of development, mainly the first or Argo-industrial transition, and it discusses the impact of nonagricultural employment on the distribution of family incomes, population growth and policy prescriptions.